2020
DOI: 10.1111/acps.13178
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional empathy in individuals at clinical high risk of psychosis

Abstract: and emotional empathy in individuals at clinical high risk of psychosis. Background: Impairments of social cognition are considered core features of schizophrenia and are established predictors of social functioning. However, affective aspects of social cognition including empathy have far less been studied than its cognitive dimensions. The role of empathy in the development of schizophrenia remains largely elusive. Methods: Emotional and cognitive empathy were investigated in large sample of 120 individuals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 70 publications
4
14
1
1
Order By: Relevance
“…The empathic concern subscale, but not the cognitive empathy subscale, of IRI was found to be compromised in UHR individuals. These results are consistent with the findings of a behaviorally-assessed empathy study which showed that, while emotional empathy in UHR individuals who later developed overt psychosis was poorer compared to HC, cognitive empathy was relatively preserved [ 18 ]. Regarding the emotional components of empathic tendency, the impairment of empathic concern in individuals at UHR for psychosis is consistent with our previous finding of reduced current pleasurable response to emotional stimuli in a laboratory setting in UHR individuals [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The empathic concern subscale, but not the cognitive empathy subscale, of IRI was found to be compromised in UHR individuals. These results are consistent with the findings of a behaviorally-assessed empathy study which showed that, while emotional empathy in UHR individuals who later developed overt psychosis was poorer compared to HC, cognitive empathy was relatively preserved [ 18 ]. Regarding the emotional components of empathic tendency, the impairment of empathic concern in individuals at UHR for psychosis is consistent with our previous finding of reduced current pleasurable response to emotional stimuli in a laboratory setting in UHR individuals [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with a previous study on behaviorally assessed empathy of UHR individuals who later developed overt psychosis; in that study, it was shown that decreased emotional empathy was related to negative symptoms. 18 In addition, this finding is consistent with previous studies that showed a negative correlation between emotional empathy and negative schizotypy in schizophrenic patients 55 and non-clinical participants. 27,56,57 Since social anhedonia, which is a negative schizotypy, is defined as a decrease in pleasure derived from interpersonal sources, decreased empathic concern in UHR individuals may reflect indifference and lower emotional reactivity to other people's experiences.…”
Section: Relationship Of Empathic Tendencies and Tom Skills With Schizotypy And Executive Functionsupporting
confidence: 91%
See 2 more Smart Citations
“…더욱이 공감경향과 마음이론 결핍은 조현병의 일차 친족 12,13) 및 조현형인격장애(schizotypal personality disorder) 환자, 14,15) 그리고 정신증고위험군(ultra-high risk for psychosis) 12,16) 에서도 관찰되기에 사회인지 손상은 조현병의 내 적표현형(endophenotype)일 수 있으며, 17) 대인관계 등 사회기 능의 결정 인자로 제시된다. [18][19][20][21] 따라서 공감경향 및 마음이론 결핍은 조현병의 핵심 손상이다.…”
unclassified